2013
DOI: 10.1371/journal.pone.0071045
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Events in Older Hospitalized Patients: Results and Reliability of a Comprehensive and Structured Identification Strategy

Abstract: BackgroundOlder patients are at high risk for experiencing Adverse Drug Events (ADEs) during hospitalization. To be able to reduce ADEs in these vulnerable patients, hospitals first need to measure the occurrence of ADEs, especially those that are preventable. However, data on preventable ADEs (pADEs) occurring during hospitalization in older patients are scarce, and no ‘gold standard’ for the identification of ADEs exists.MethodologyThe study was conducted in three hospitals in the Netherlands in 2007. ADEs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 64 publications
(104 reference statements)
2
52
2
2
Order By: Relevance
“…The results from the latter study may differ from ours as Klopotowska et al, 14 had a senior physicianpharmacist team as reviewers whereas our study involved reviewers from various disciplines. 14 Also, Klopotowska et al, 14 limited their patient population to those over the age of 65 who were receiving more than five medications, and restricted the type of AEs collected to those that arose from medications whereas our study used no such limits. 14 Individuals using the SAVES-SCI should be trained on how to grade AEs, particularly for the pre-and post-surgical intervention AEs with low kappa values.…”
Section: Identifying Versus Grading Aescontrasting
confidence: 68%
See 2 more Smart Citations
“…The results from the latter study may differ from ours as Klopotowska et al, 14 had a senior physicianpharmacist team as reviewers whereas our study involved reviewers from various disciplines. 14 Also, Klopotowska et al, 14 limited their patient population to those over the age of 65 who were receiving more than five medications, and restricted the type of AEs collected to those that arose from medications whereas our study used no such limits. 14 Individuals using the SAVES-SCI should be trained on how to grade AEs, particularly for the pre-and post-surgical intervention AEs with low kappa values.…”
Section: Identifying Versus Grading Aescontrasting
confidence: 68%
“…The literature reports mixed results in this area. Sharek et al, 15 reported higher kappa for identifying than grading AEs, whereas Klopotowska et al, 14 reported higher agreement for grading than identifying AEs for both intra-rater and inter-rater reliability. The results from the latter study may differ from ours as Klopotowska et al, 14 had a senior physicianpharmacist team as reviewers whereas our study involved reviewers from various disciplines.…”
Section: Identifying Versus Grading Aesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies show that number of prescribed medicines increases with aging [10]. Polypharmacy causes an increase in the risk of side effects and interaction between medicines, treatment costs, hospitalization requirements, rates of incompatibility to medical treatment and resulting problems [11].…”
Section: Polypharmacymentioning
confidence: 99%
“…20 In this study we also explicitly included temporary harm, emotional or psychological harm, pain requiring intervention and abnormal laboratory values, as used in other recent research. 21,22 Adverse Medication (Drug) Event…”
Section: Incidentmentioning
confidence: 99%